2019
DOI: 10.2196/12505
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Increasing Treatment Adherence: Systematic Review

Abstract: Background It is estimated that 20% to 50% of patients do not take their medication correctly, and this leads to increased morbidity and inefficacy of therapeutic approaches. Fostering treatment adherence is a priority objective for all health systems. The growth of mobile apps to facilitate therapeutic adherence has significantly increased in recent years. However, the effectiveness of the apps for this purpose has not been evaluated. Objective This study aimed to anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 33 publications
(251 reference statements)
3
85
1
5
Order By: Relevance
“…For example, compared to usual care, a mobile health technology–supported disease management model for atrial fibrillation resulted in improvements in patient quality of life [ 17 ]. Patient adherence and disease management may also be improved with the support of treatment management apps [ 16 , 18 , 19 ]. For example, a 2019 systematic literature review of studies investigating mobile apps as a method to improve treatment adherence identified 11 studies of patients with a variety of diseases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to usual care, a mobile health technology–supported disease management model for atrial fibrillation resulted in improvements in patient quality of life [ 17 ]. Patient adherence and disease management may also be improved with the support of treatment management apps [ 16 , 18 , 19 ]. For example, a 2019 systematic literature review of studies investigating mobile apps as a method to improve treatment adherence identified 11 studies of patients with a variety of diseases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wolf and Kelly defined the term quantified-self in 2007 which, according to Swan [25], can be defined as "any individual engaged in the self-tracking of any kind of biological, physical, behavioral, or environmental information, as a proactive stance toward obtaining information and acting on it." This author also provided several examples of different quantified self-data, such as: Swan (10) defined quantified self-tracking as the collection of information (physical, biological, environmental, or behavioral) that can be measured by an individual. The technologies should make it easy to use and access this information, and the data should be accurate and suitable for analysis.…”
Section: State Of the Artmentioning
confidence: 99%
“…Park et al [9] carried out a study of the efficacy of mobile phone interventions and demonstrated that personalized feedback has positive effects on medication adherence. Other studies have also been carried out to evaluate the effectiveness of technological means to increase adherence to treatment [10][11][12], although it should be noted that some applications only remind the patient to take medication. In contrast, other applications have more content, such as educational interventions or rehabilitation exercises [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Similar pillboxes have been in use for several decades for various medications. With the use of such an ordinary pillbox, patients can selfmanage their medications, identify whether they have taken the dose, and minimize the rate of medication errors [52]. Previous studies found that individuals who used a pillbox had better adherence to treatment [53][54][55].…”
Section: Introductionmentioning
confidence: 99%